The Effect of Compost, Host Resistance, and Chemical Treatment Interaction on Complex Wilt Disease Management on Hot Pepper (Capsicum annuum L.) in Jabi Tehena District, Northwestern Ethiopia - Mastewal Alehegn; Chemeda Fininsa; Habtamu Terefe; Mashilla Dejene; Wassu Mohammed (The Scientific World Journal, 2025)
Hot pepper is a vital vegetable crop traditionally valued for its commercial importance and role in rural economies, with its fruits consumed fresh, dried, processed, or used as condiments. Hot pepper wilt, a complex disease caused by various soilborne pathogens, significantly influenced hot pepper crops. This study is aimed at evaluating the combined effects of compost application, host resistance, and chemical treatments on seeds and seedlings in managing this disease, as well as its effect on yield. Eighteen treatment combinations were tested in a split–split plot design with three replications. The findings showed highly significant differences (p≤0.001) in disease severity, area under disease progress curve (AUDPC), and agronomic traits across the treatment combinations. The study found that the Melka Zala variety, when treated with Apron Star and transplanted into compost-treated plots, exhibited the lowest disease severity (23%), AUDPC (478.33%-days), and disease progress rate (0.0034 units/day). In contrast, the Mareko Fana variety, grown in compost-untreated and control plots, showed the highest disease severity (54%), AUDPC (1426.67%-days), and disease progress rate (0.0114 units/day). Additionally, Melka Zala yielded the highest marketable fruit yield (2.42 t ha−1) and total fruit yield (2.47 t ha−1) when the seeds and seedlings were treated with Apron Star Fungicide and transplanted into compost-treated plots. Treating Melka Zala seeds and seedlings with Apron Star fungicide and transplanting them into compost-treated plots resulted in twice the net benefit and marketable fruit yield compared to other treatment combinations. In conclusion, using the Melka Zala variety treated with Apron Star and grown in compost-treated plots effectively controlled the disease and improved yield, suggesting this approach as a viable strategy for farmers in the study area and similar agroecological zones to manage wilt disease.